Paul's Cross and the culture of persuasion in England, 1520-1640 - Kirby, W. J. Torrance; Stanwood, P. G. (Studies in the history of Christian traditions., 2014)
By reconstructing the history of sermons preached at Paul's Cross between 1520 and 1640 this collection of essays examines the flourishing 'culture of persuasion' which transformed England's political and religious identities and fostered a nascent public sphere.